The Impact of Employee to Customer Relationship on Customer Loyalty - Widodo, Teguh; Egin Gumilang, Dhimas (International Journal of Engineering and Technology, 2019)
Many previous studies have discussed the role of customer relationship management (CRM), unfortunately there areÂ limited research that reveals relationship between CRM dimensions and performance in internet service provider industry. This study provides a conceptual framework of the antecedent of customer loyalty involving CRM dimensions, particularyÂ employee to customer relationship (ECR) and customer to customer relationship (CCR),Â and the role of customer satisfaction construct in mediating the effect of those dimensions to customer loyalty Data were collected through an online survey to get a sample of 250 internet users Indihome Telkom Bandung for three months starting from the beginning of year 2016. The result is that while the ECR does not have a direct impact on customer loyalty, but through the mediating role of customer satisfaction variable, ECR has an indirect impact on customer loyalty. This research recomands to practicies that in order to increase customer loyalty to the firm, to focus on ECR rather then on CCRÂ Â